1836 : (26 - 4 * у) - 12 = 90
1836 : (26 - 4 * у) = 90 + 12
1836 : (26 - 4 * у) = 102
26 - 4 * у = 1836 : 102
26 - 4 * у = 18
4 * у = 26 - 18
4 * у = 8
у = 8 : 4
у = 2
Проверка:
1836 : (26 - 4 * 2) - 12 = 90
1836 : (26 - 8) - 12 = 90
1836 : 18 - 12 = 90
102 - 12 = 90
90 = 90
1836:(26-4y)-12=90
1836:(26-4y)=102
26-4y=18
4у=8
у=2
1836 : (26 - 4 * у) - 12 = 90
1836 : (26 - 4 * у) = 90 + 12
1836 : (26 - 4 * у) = 102
26 - 4 * у = 1836 : 102
26 - 4 * у = 18
4 * у = 26 - 18
4 * у = 8
у = 8 : 4
у = 2
Проверка:
1836 : (26 - 4 * 2) - 12 = 90
1836 : (26 - 8) - 12 = 90
1836 : 18 - 12 = 90
102 - 12 = 90
90 = 90
1836:(26-4y)-12=90
1836:(26-4y)=102
26-4y=18
4у=8
у=2